The Role Of The Al Islam Sidoarjo Foundation In Empowering The Local Economy: A Study Of The Relationship Between Religious Education And The Strengthening Of MSMEs In The Surrounding Environment - Laila Azkiya Ulinnuha; Mohammad Kurjum; Tri Sudarwanto (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study examines the role of the Al Islam Sidoarjo Foundation in local economic empowerment through linking religious education and MSME strengthening. MSMEs contribute 61.07% to Indonesia's GDP and employ 97% of the workforce, yet the systemic connection between religious institutions and local MSMEs remains underexplored. Using a qualitative approach with a case study method, data was collected through in-depth interviews, field observations and review of foundation documents. Results reveal the foundation's strategic role across three dimensions: social, spiritual, and economic empowerment through routine educational activities, inclusive MSME policies, and religious social activities generating economic multiplier effects. These activities increase MSME income both during daily routine activities and significantly during major religious events. The Al Islam Foundation functions beyond Islamic education, acting as a community economic empowerment agent fostering sustainable welfare through spiritual-economic value synergy.